Digital method for lip print analysis: A New approach - Prabhu, Rachana V. (Medknow Publications & Media Pvt Ltd, 2013)
AIM: To evaluate the uniqueness and to define a standard method for the analysis of lip prints. MATERIALS AND METHODS: Lip prints of 100 students were taken using Scotch tape without any distortion. These prints were then scanned for the digital analysis. Using Adobe Photoshop 7 software an attempt was made to trace each and every line using Suzuki and Tsuchihashi's classification. Weighted value scoring system was used to check for the uniqueness of the lip prints. RESULTS: No two lip prints had exactly matching scores in all four Quadrants. No statistically significant difference was found in the change of pattern in lip print images collected after 12 months from the same individual. With digital analysis, up to 15 lines were traceable in 66%, 71%, 52% and 51% of Quadrant I, II, III and IV respectively. CONCLUSION: Lip prints are unique to an individual. The digital method of analyzing lip print images serves better visualization, ease in identification and recording of the lip print pattern. Weighted Value Scoring system can be considered as a standard method for determining the uniqueness of the lip prints.